The Influence of the Visionary Leadership of Madrasah Heads, Organizational Culture and Motivation for Achievement on the Performance - Yazid, Abu; Ahmad, Gofur; Dewi, Happy Indira (International Journal of Educational Narratives, 2024)
Background:Changes in the education sector present significant challenges and problems for communities, influencing various sectors, including the social domain. Educational institutions, such as madrasahs, are crucial in addressing these challenges. Purpose:This study aims to analyze the impact of the visionary leadership of madrasah heads, organizational culture, and achievement motivation on teacher performance. Methods:A quantitative approach with path analysis was used in this research. Data collection was conducted through a questionnaire, followed by normality, validity, and reliability tests. The data were processed using SPSS software for path analysis. Results:The study found that visionary leadership of madrasah heads, organizational culture, and motivation for achievement significantly influenced teacher performance. Conclusions:The findings suggest that strengthening visionary leadership, enhancing organizational culture, and fostering achievement motivation can improve teacher performance in madrasahs. However, the study is limited to madrasah aliyah (high school) level, and future research is recommended at higher educational levels.